Answer: 68*
Step-by-step explanation: In pic
Im assuming you are supposed to factor this problem considering there is no = sign. starting with numbers, you can factor, or divide, both of those numbers by 9. moving on to letters, both terms have a “y” attached to them, so you can take out a y as well. leaving you with the simplified equation being
9y (2x-3)
First Factor.
![(x-1)^5 = x^5 -5x^4+10x^3 -10x^2+5x-1](https://tex.z-dn.net/?f=%28x-1%29%5E5%20%3D%20x%5E5%20-5x%5E4%2B10x%5E3%20-10x%5E2%2B5x-1)
![g(x) = y = (x-1)^5](https://tex.z-dn.net/?f=g%28x%29%20%3D%20y%20%3D%20%28x-1%29%5E5)
Find inverse by solving for 'x'
Answer:
60
Step-by-step explanation: